2022
DOI: 10.3389/fneur.2022.1033327
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Recreational nitrous oxide abuse triggered peripheral neuropathy possibly through the immune-mediated pathogenesis

Abstract: Nitrous oxide (N2O), commonly known as laughing gas, is widely used in clinical practice and food industry. However, an increasing number of young people have been abusing N2O for recreational purpose, resulting in many functional disorders and sometimes irreversible nerve damage. We present the case of a 20-year-old N2O abuser who gradually developed peripheral neuropathy after continuously inhaling N2O for 2 months. The neurological symptoms of the patient had kept exacerbation for the next 2 months until sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Neurological symptoms have developed over a median of 21 days, in line with previous data 14,32,37,48,62,65 . The clinical manifestations extracted from the literature confirmed that impaired proprioception and coordination and decreased superficial sensation were the most prevalent manifestations 20 . Classically, spinal cord MRI is characterized by the inverted V-sign on T2-weighted images and the absence of contrast enhancement 69,70 .…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Neurological symptoms have developed over a median of 21 days, in line with previous data 14,32,37,48,62,65 . The clinical manifestations extracted from the literature confirmed that impaired proprioception and coordination and decreased superficial sensation were the most prevalent manifestations 20 . Classically, spinal cord MRI is characterized by the inverted V-sign on T2-weighted images and the absence of contrast enhancement 69,70 .…”
Section: Discussionsupporting
confidence: 75%
“…14,32,37,48,62,65 The clinical manifestations extracted from the literature confirmed that impaired proprioception and coordination and decreased superficial sensation were the most prevalent manifestations. 20 Classically, spinal cord MRI is characterized by the inverted V-sign on T2-weighted images and the absence of contrast enhancement. 69,70 Only a few cases reported in the literature have shown a minimal contrast enhancement 15,17,18,51 due to the breakdown of the blood-brain barrier related to inflammation and perivascular demyelination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The excessive use of N 2 O can lead to considerable demyelination of peripheral axons, and subsequently to muscle weakness and even paralysis, especially in the lower limbs (van Amsterdam et al, 2015). There is no conventional definition of what is considered excessive use, but some case reports state use patterns of over a 500 metal bulbs/balloons per day (Lewis et al, 2021), although the occurrence of peripheral neuropathy has also been reported after the use of 10 bulbs per day (Cartner et al, 2007; Dong et al, 2022). It is not clear if comparatively modest usage patterns also significantly introduce the risk of peripheral demyelination.…”
Section: Characteristics and Risks Of Recreational Nitrous Oxide Use ...mentioning
confidence: 99%
“…Furthermore, fatalities resulting from N₂O inhalation have been documented (9). Currently, only a limited number of studies have focused on the peripheral neuropathy caused by abusive inhalation of nitrous oxide (10)(11)(12), highlighting a lack of awareness regarding the toxicity associated with N₂O abuse. Therefore, this study aims to comprehensively outline the clinical characteristics, mechanisms, and management strategies for N₂O-associated peripheral neuropathy.…”
Section: Introductionmentioning
confidence: 99%